2021
DOI: 10.1002/csr.2162
|View full text |Cite
|
Sign up to set email alerts
|

How corporate social responsibility initiatives affect the choice of a bank: Empirical evidence of Italian context

Abstract: For all firms, it is imperative to identify and understand the factors that influence consumers purchasing behaviors and, specifically, identify how customer demographics relate to corporate social responsibility (CSR) activities. However, limited research exists on banking consumer's preferences and responses towards different CSR initiatives. Therefore, using an exploratory survey consisting of 250 received responses of attitudes and perceptions from customers of Italian savings banks, we investigate the int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 74 publications
0
8
0
Order By: Relevance
“…Researchers underline that SMEs typically suffer from a shortage of all the competencies needed to implement innovations (Alvarez & Iske, 2015; Andersson et al, 2020). Establishing a partnership with customers (a highly regarded determinant) and suppliers is often an optimal way to bridge the aforementioned gaps in competencies and financial resources (Jové‐Llopis & Segarra‐Blasco, 2018; Lagasio et al, 2021). Nowadays, the presence of many specific types of external supports could mitigate the financial needs of innovative SMEs.…”
Section: The Interpretative Framework and The Hypothesesmentioning
confidence: 99%
“…Researchers underline that SMEs typically suffer from a shortage of all the competencies needed to implement innovations (Alvarez & Iske, 2015; Andersson et al, 2020). Establishing a partnership with customers (a highly regarded determinant) and suppliers is often an optimal way to bridge the aforementioned gaps in competencies and financial resources (Jové‐Llopis & Segarra‐Blasco, 2018; Lagasio et al, 2021). Nowadays, the presence of many specific types of external supports could mitigate the financial needs of innovative SMEs.…”
Section: The Interpretative Framework and The Hypothesesmentioning
confidence: 99%
“…Based on the theory of reasoned actions [63], personal attitudes and behaviors have a relationship. According to [64], in the Italian banking industry, CSR practices related to the environment, society, and ecosustainable projects are important; at the same time, customers believe that there is a link between CSR practices and their choice of banks. In the hospitality industry, during the COVID-19 pandemic, CSR practices encouraged customers to prepay services [65].…”
Section: Purchase Intentionmentioning
confidence: 99%
“…A number of studies have demonstrated that CSR practices had a positive effect on BL (e.g., Štreimikiene & Ahmed, 2021;Lacap et al, 2021;Luo &. Bhattacharya, 2006;Tao & Ji, 2020;Hafez, 2015;Lagasio et al, 2021;Dawood, 2019). In addition, other studies revealed that BT has a positive effect on BL (e.g., Wu & Liu, 2022;Haudi et al, 2022;Tan et al, 2022;Benson, 2022;Adha & Utami, 2021;Zehir et al, 2011).…”
Section: 3the Moderating Role Of Brand Trustmentioning
confidence: 99%
“…CSR practices have a significant effect, not only on shareholders, employees, and suppliers, but also on all other stakeholders, particularly customers (e.g., Tan et al, 2022;Nazir et al, 2021;Mahmood & Bashir, 2020;Aljarah & Ibrahim, 2020;Lin & Chung, 2019). CSR, therefore, may be used as a method to boost consumer's BL (Tan et al, 2022;Lagasio et al, 2021;Farid et al, 2019;Rahman et al 2019). However, limited research has been conducted to gage a banking consumer's preferences and responses to various CSR.…”
Section: Introductionmentioning
confidence: 99%